2021
DOI: 10.1136/bjophthalmol-2020-318494
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity function in patients with macular disease and good visual acuity

Abstract: IntroductionContrast sensitivity function (CSF) may better estimate a patient’s visual function compared with visual acuity (VA). Our study evaluates the quick CSF (qCSF) method to measure visual function in eyes with macular disease and good letter acuity.MethodsPatients with maculopathies (retinal vein occlusion, macula-off retinal detachment, dry age-related macular degeneration and wet age-related macular degeneration) and good letter acuity (VA ≥20/30) were included. The qCSF method uses an intelligent al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
2
23
1
Order By: Relevance
“…A recent qCSF implementation with a 10-letter identification task enabled assessment of the CSF with a 0.10 log unit standard deviation in about 20 trials (approximately 2 minutes) and reduced the standard deviation of the estimates by 50% ( Hou, Lesmes, Bex, Dorr, & Lu, 2015 ). Accurate and precise qCSF estimates have been obtained in both normal ( Reynaud, Tang, Zhou, & Hess, 2014 ; Rosén, Lundström, Venkataraman, Winter, & Unsbo, 2014 ) and clinical populations ( Hou, Huang, Lesmes, Feng, Tao, Zhou, & Lu, 2010 ; Jia, Zhou, Lu, Lesmes, & Huang, 2015 ; Joltikov, de Castro, Davila, Anand, Khan, Farbman, Jackson, Johnson, & Gardner, 2017 ; Lesmes, Jackson & Bex, 2013 ; Lesmes, Wallis, Jackson, & Bex, 2013 ; Lesmes, Wallis, Lu, Jackson, & Bex, 2012 ; Lin, Mihailovic, West, Johnson, Friedman, Kong, & Ramulu, 2018 ; Ou, Lesmes, Christie, Denlar, & Csaky, 2021 ; Ramulu, Dave, & Friedman, 2015 ; Rosen, Jayaraj, Bharadwaj, Weeber, Van der Mooren, & Piers, 2015 ; Stellmann, Young, Pottgen, Dorr, & Heesen, 2015 ; Thomas, Silverman, Vingopoulos, Kasetty, Yu, Kim, Omari, Joltikov, Choi, Kim, Zacks, & Miller, 2021 ; Vingopoulos, Wai, Katz, Vavvas, Kim, & Miller, 2021 ; Wai, Vingopoulos, Garg, Kasetty, Silverman, Katz, Laíns, Miller, Husain, Vavvas, Kim, & Miller, 2021 ; Yan, Hou, Lu, Hu, & Huang, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent qCSF implementation with a 10-letter identification task enabled assessment of the CSF with a 0.10 log unit standard deviation in about 20 trials (approximately 2 minutes) and reduced the standard deviation of the estimates by 50% ( Hou, Lesmes, Bex, Dorr, & Lu, 2015 ). Accurate and precise qCSF estimates have been obtained in both normal ( Reynaud, Tang, Zhou, & Hess, 2014 ; Rosén, Lundström, Venkataraman, Winter, & Unsbo, 2014 ) and clinical populations ( Hou, Huang, Lesmes, Feng, Tao, Zhou, & Lu, 2010 ; Jia, Zhou, Lu, Lesmes, & Huang, 2015 ; Joltikov, de Castro, Davila, Anand, Khan, Farbman, Jackson, Johnson, & Gardner, 2017 ; Lesmes, Jackson & Bex, 2013 ; Lesmes, Wallis, Jackson, & Bex, 2013 ; Lesmes, Wallis, Lu, Jackson, & Bex, 2012 ; Lin, Mihailovic, West, Johnson, Friedman, Kong, & Ramulu, 2018 ; Ou, Lesmes, Christie, Denlar, & Csaky, 2021 ; Ramulu, Dave, & Friedman, 2015 ; Rosen, Jayaraj, Bharadwaj, Weeber, Van der Mooren, & Piers, 2015 ; Stellmann, Young, Pottgen, Dorr, & Heesen, 2015 ; Thomas, Silverman, Vingopoulos, Kasetty, Yu, Kim, Omari, Joltikov, Choi, Kim, Zacks, & Miller, 2021 ; Vingopoulos, Wai, Katz, Vavvas, Kim, & Miller, 2021 ; Wai, Vingopoulos, Garg, Kasetty, Silverman, Katz, Laíns, Miller, Husain, Vavvas, Kim, & Miller, 2021 ; Yan, Hou, Lu, Hu, & Huang, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our recently published work [79], our team has also examined a large cohort of 151 patients who retained good visual acuity and with different macular diseases including Our team has also previously reported on the qCSF method in eyes with maculaoff rhegmatogenous retinal detachment (RRD) after surgical repair. Eyes with a history of macula-off RRD had statistically significant reductions in AULCSF and in contrast sensitivity thresholds across all spatial frequencies compared to healthy age-matched control eyes [74].…”
Section: Current Applications Of the Qcsf Methods In Retinal Diseasesmentioning
confidence: 99%
“…In our recently published work [79], our team has also examined a large cohort of 151 patients who retained good visual acuity and with different macular diseases including RVO, history of macula RRD, and dry and wet AMD. Similarly, reductions in AULCSF and contrast thresholds at all spatial frequencies were found to be significantly reduced in eyes with various macular diseases with VA as good as 20/30, and even in the eyes with VA 20/20 −1 , compared to 93 healthy control eyes.…”
Section: Current Applications Of the Qcsf Methods In Retinal Diseasesmentioning
confidence: 99%
“…Many studies have demonstrated that CSF could reflect the correlation between subjective visual function and vision-guided activities in daily life ( 42 44 ). Wai et al showed that eyes with macular disease and good VA have significantly reduced CSF compared with healthy control eyes ( 45 ), and they thought CSF may be able to explain some subjective visual complaints and patients' bad visual experiences while visual acuity may not. Shamsi et al have even put forward the idea that the visual acuity and contrast sensitivity in the foveal region were dissociative ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that retinal structure is closely related to contrast sensitivity ( 31 , 45 , 47 ). Wang found that the retinal inner layer is associated with reduced contrast sensitivity in retinal vein occlusion ( 47 ).…”
Section: Discussionmentioning
confidence: 99%